2012
DOI: 10.48550/arxiv.1209.5719
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Quasifuchsian state surfaces

David Futer,
Efstratia Kalfagianni,
Jessica S. Purcell

Abstract: This paper continues our study, initiated in [12], of essential state surfaces in link complements that satisfy a mild diagrammatic hypothesis (homogeneously adequate). For hyperbolic links, we show that the geometric type of these surfaces in the Thurston trichotomy is completely determined by a simple graph-theoretic criterion in terms of a certain spine of the surfaces. For links with A-or B-adequate diagrams, the geometric type of the surface is also completely determined by a coefficient of the colored Jo… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2013
2013
2014
2014

Publication Types

Select...
1
1

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(5 citation statements)
references
References 13 publications
0
5
0
Order By: Relevance
“…In fact, Garoufalidis and Le have studied the "higher order" stability properties of the colored Jones polynomials and they showed that the stable coefficients of the polynomials J K (n + 1, q) give rise to infinitely many q-series with interesting number theoretic and physics connections. On the other hand, the work of Futer, Kalfagianni and Purcell [8,9,10,12,11] showed that certain stable coefficients of J K (n + 1, q) encode information about incompressible surfaces in knot complements and their geometric types and have direct connections to hyperbolic geometry. See also discussion below.…”
Section: Stabilization Properties Of Jones Polynomialsmentioning
confidence: 99%
See 3 more Smart Citations
“…In fact, Garoufalidis and Le have studied the "higher order" stability properties of the colored Jones polynomials and they showed that the stable coefficients of the polynomials J K (n + 1, q) give rise to infinitely many q-series with interesting number theoretic and physics connections. On the other hand, the work of Futer, Kalfagianni and Purcell [8,9,10,12,11] showed that certain stable coefficients of J K (n + 1, q) encode information about incompressible surfaces in knot complements and their geometric types and have direct connections to hyperbolic geometry. See also discussion below.…”
Section: Stabilization Properties Of Jones Polynomialsmentioning
confidence: 99%
“…At each crossing of D, we connect the pair of neighboring disks by a half-twisted band to construct a surface S A ⊂ S 3 whose boundary is K. See Figure 1 for an example. By the work of the first author with Futer and Purcell [10,12], the invariant T K (q) detects the geometric types of the surface S A (D) and contains a lot of information about the geometric structures of of the complements S 3 \\S A (D) and S 3 K. For example, combining Corollary 3.6 with results of [10,12] we have the following; for terminology and more details the reader is referred to the original references.…”
Section: 4mentioning
confidence: 99%
See 2 more Smart Citations
“…It seems that the main connections between them are the volume conjecture, which generalizes Kashaevs conjecture for hyperbolic knots (see [34] and [23]), the AJ-conjecture (see [18] and [32]) and the relations, via certain incompressible surfaces in a link complement, of the extremal coefficients of the n-colored Jones polynomial with the geometric structure of the link complement (see [15], [16], [17]).…”
Section: Resultsmentioning
confidence: 99%